Chronic cocaine but not chronic amphetamine use is associated with perseverative responding in humans - Ersche, Karen D.; Roiser, Jonathan P.; Robbins, Trevor W.; Sahakian, Barbara J. (Psychopharmacologia, 2008)
Rationale Chronic drug use has been associated with increased impulsivity and maladaptive behaviour, but the underlying mechanisms of this impairment remain unclear. We investigated the ability to adapt behaviour according to changes in reward contingencies, using a probabilistic reversal-learning task, in chronic drug users and controls. Materials and methods Five groups were compared: chronic amphetamine users ( n = 30); chronic cocaine users ( n = 27); chronic opiate users ( n = 42); former drug users of psychostimulants and opiates ( n = 26); and healthy non-drug-taking control volunteers ( n = 25). Participants had to make a forced choice between two alternative stimuli on each trial to acquire a stimulus–reward association on the basis of degraded feedback and subsequently to reverse their responses when the reward contingencies changed. Results Chronic cocaine users demonstrated little behavioural change in response to the change in reward contingencies, as reflected by perseverative responding to the previously rewarded stimulus. Perseverative responding was observed in cocaine users regardless of whether they completed the reversal stage successfully. Task performance in chronic users of amphetamines and opiates, as well as in former drug users, was not measurably impaired. Conclusion Our findings provide convincing evidence for response perseveration in cocaine users during probabilistic reversal-learning. Pharmacological differences between amphetamine and cocaine, in particular their respective effects on the 5-HT system, may account for the divergent task performance between the two psychostimulant user groups. The inability to reverse responses according to changes in reinforcement contingencies may underlie the maladaptive behaviour patterns observed in chronic cocaine users but not in chronic users of amphetamines or opiates.